2014
DOI: 10.1016/j.bbapap.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous and specific recognition among ephrins and Eph receptors

Abstract: Eph-ephrin interactions control the signal transduction between cells and play an important role in carcinogenesis and other diseases. The interactions between Eph receptors and ephrins of the same subclass are promiscuous; there are cross-interactions between some subclasses, but not all. To understand how Eph-ephrin interactions can be both promiscuous and specific, we investigated sixteen energy landscapes of four Eph receptors (A2, A4, B2, and B4) interacting with four ephrin ligands (A1, A2, A5, and B2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 77 publications
(85 reference statements)
1
39
0
Order By: Relevance
“…37,38 Conformational dynamics permits both promiscuity and specificity. 34,[39][40][41][42][43][44] Protein complex formation redistributes the dynamics, 45,46 allowing allosteric signaling through protein domains. Antibody-antigen recognition, which is associated with structural transitions through inherent conformational flexibility, [5][6][7] involves conformational selection.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Conformational dynamics permits both promiscuity and specificity. 34,[39][40][41][42][43][44] Protein complex formation redistributes the dynamics, 45,46 allowing allosteric signaling through protein domains. Antibody-antigen recognition, which is associated with structural transitions through inherent conformational flexibility, [5][6][7] involves conformational selection.…”
Section: Discussionmentioning
confidence: 99%
“…Human EphA receptors (EphA1-A8 and EphA10) preferentially bind to the ephrin A ligands, whereas human EphB receptors (EphB1-B4 and EphB6) bind to the ephrin B ligands. However, promiscuous binding of EphA receptors to ephrin-Bs, or EphB receptors to ephrin-As have been shown [5][6][7]. The specificity of the Eph receptors appears to be dictated by their ectodomains, as shown in a chimera experiment [8].…”
mentioning
confidence: 98%
“…The 14 known members of the Eph receptor family are further divided into two subfamilies: the nine EphA (A1-A8, A10) receptors which primarily bind to GPI (glycosyl phosphatidylinositol)-linked ephrin-A ligands, and the five EphB (B1-B4, B6) receptors which primarily bind to transmembrane ephrin-B ligands ( Janes et al, 2012 ; Sloniowski and Ethell, 2012 ). Despite these ligand preferences, multiple studies have shown that cross-subfamily binding is also possible and the Eph receptors' ligand specificities are not absolute ( Kullander and Klein, 2002 ; Himanen et al, 2004 ; Noberini et al, 2012 ; Dai et al, 2014 ). Nevertheless, in most physiologic cases, both the receptors and their ligands are membrane-bound.…”
Section: Introductionmentioning
confidence: 99%